Democracia participativa y crisis de la política. La experiencia de los planes comunitarios - Marchioni, Marco (Cuadernos de Trabajo Social, 2006)
The crisis in politics and in the parties is evident. One may speak of a crisis of militancy and of affiliation; however, the parties continue to be the fundamental elements of the system. Political life is not based on participation, while community plans demand the input of the population, the authentic protagonist of the process. In order to put into play community plans it is necessary to have an adequate methodology, a community team which guides the process and the citizens of an area ready to improve its situation. Participation requires open and flexible organizations.